Strategies to improve the retention and availability of soil water - Klein, Claudia; Klein, Vilson Antonio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Soil is known for its great potential in water storage. However, there would be ways to enhance the water storage in the soil specially in times of drought? It is known that water dynamics is governed by numerous factors, such as precipitation, infiltration, soil structure, organic matter, among others, so it is difficult to predict and improve. This review aims to highlight the main management techniques to improve the retention and availability of water for the farm. Techniques such as application of organic matter, biochar, synthetic polymers (hydrogels), construction of underground dams and reservoirs under the ground (Dammer Diker) have shown promising results in water retention in the soil, although some of these require further study. For food production increases with quality and without requiring additional irrigation is necessary that the studies on this topic continue, especially in the field and in typical soils in Brazil..